Pelatihan Metode Jarimatika pada Siswa Kelas II SD Negeri 1 Lu Tawar - Septia Wahyuni; Elfi Rahmadhani (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
This service aims to provide knowledge about multiplication and division arithmetic operations, introduce the Jarimatika method that is easily understood by students. The method used is in the form of lectures, practice and exercises by providing learning materials for Jarimatika and questions that must be discussed in class. The training was carried out in Class II of the State Elementary School 1 Lut Tawar with a total of 25 students. The results of this service are: 1) students gain new knowledge in solving multiplication and division operations, 2) students have high motivation to get high math scores.